A broad-host-range lytic phage vB_VhaS-R18L as a candidate against vibriosis - Cai, Lanlan; Tian, Yuan; Li, Ziqiang; Yang, Yunlan; Ai, Chunxiang; Zhang, Rui (Frontiers in Microbiology, 2023)
Vibriosis is one of the most common bacterial diseases that cause high rates of mortality and considerable economic losses in aquaculture. Phage therapy has been considered as a promising alternative method to antibiotics in the biocontrol of infectious diseases. Genome sequencing and characterization of the phage candidates are prerequisites before field applications to ensure environmental safety. In this study, a lytic phage, named vB_VhaS-R18L (R18L), was isolated from the coastal seawater of Dongshan Island, China. The phage was characterized in terms of morphology, genetic content, infection kinetics, lytic profile, and virion stability. Transmission electronic microscopy indicated that R18L is siphovirus-like, comprising an icosahedral head (diameter 88.6 ± 2.2 nm) and a long noncontractile tail (225 × 11 nm). Genome analysis indicated R18L to be a double-stranded DNA virus with a genome size of 80,965 bp and a G+C content of 44.96%. No genes that encode known toxins or genes implicated in lysogeny control were found in R18L. A one-step growth experiment showed that R18L had a latent period of approximately 40 min and a burst size of 54 phage particles per infected cell. R18L showed lytic activity against a wide range of at least five Vibrio species (V. alginolyticus, V. cholerae, V. harveyi, V. parahemolyticus, and V. proteolyticus). R18L was relatively stable at pH 6–11 and at temperatures ranging from 4°C to 50°C. The broad lytic activity across Vibrio species and the stability in the environment make R18L a potential candidate for phage therapy in controlling vibriosis in aquaculture systems.